Role of curcumin in oral infection and inflammation - Shunmugavelu, Karthik; Bhaskar, Gautam (GMS Hygiene and Infection Control)
Curcumin, which is a polyphenol from the rhizomes of Curcuma longa, has been found to possess anti-inflammatory, antioxidant, and antimicrobial activities. This systematic review examines the effectiveness of curcumin in treating oral inflammation, e.g., periodontal diseases, gingivitis, oral lichen planus (OLP), and radiation-induced oral mucositis (ROM). The studies in this review assess different curcumin formulations, including gels, hydrogels, nano-curcumin, and mouthwashes, as adjunctive agents in oral inflammatory diseases. The studies indicate that curcumin significantly decreases clinical markers of inflammation, improves healing, and reduces patient discomfort, warranting its use as an adjunctive therapeutic agent.